The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-84444-x
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial delivery of nanoparticles encapsulated with 1α, 25-dihydroxyvitamin D3 attenuates restenosis in a murine angioplasty model

Abstract: Percutaneous transluminal angioplasty (PTA) of stenotic arteriovenous fistulas (AVFs) is performed to maintain optimal function and patency. The one-year patency rate is 60% because of venous neointimal hyperplasia (VNH) and venous stenosis (VS) formation. Immediate early response gene X-1 (Iex-1) also known as Ier3 increases in response to wall shear stress (WSS), and can cause VNH/VS formation in murine AVF. In human stenotic samples from AVFs, we demonstrated increased gene expression of Ier3. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In support of the importance of the adventitia in vascular stenoses, we note studies where adventitial injury and activation is associated with vascular stenosis [24][25][26] and also studies by Misra et al in a mouse AVF stenosis model where adventitial therapy with a blocker of CX3CR1 [27] reduced peri-anastomotic stenosis and adventitial delivery of Vitamin D, both post angioplasty in a mouse model [28], and also reduced venous stenosis.…”
Section: Discussionsupporting
confidence: 78%
“…In support of the importance of the adventitia in vascular stenoses, we note studies where adventitial injury and activation is associated with vascular stenosis [24][25][26] and also studies by Misra et al in a mouse AVF stenosis model where adventitial therapy with a blocker of CX3CR1 [27] reduced peri-anastomotic stenosis and adventitial delivery of Vitamin D, both post angioplasty in a mouse model [28], and also reduced venous stenosis.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study performed in a pig AVF model with chronic kidney disease showed that adventitial delivery of poly(lactic-co-glycolic acid) (PLGA) nanoparticles encapsulated with 1α,25(OH) 2 D3 (1,25 NP), compared to vehicle controls, delivered to the adventitia of the outflow vein after AVF creation reduced venous stenosis formation (Figure 5) by decreasing inflammation and fibrosis 46 . Another study using a mouse model showed that PLGA nanoparticles encapsulated with 1α,25(OH) 2 D3 and delivered to the adventitia of the outflow vein after angioplasty decreased venous neointimal hyperplasia and restenosis by decreasing inflammation and apoptosis pathways 47 . Other studies have demonstrated that using microparticles coated with simvastatin to the adventitia of the outflow vein of experimental animals can reduce venous stenosis formation 48 .…”
Section: Periadventitial Drug Therapymentioning
confidence: 99%